Efficient imputation of missing markers in low-coverage genotyping-by-sequencing data from multi-parental crosses - Huang, B Emma; Raghavan, Chitra; Mauleon, Ramil; Broman, Karl W.; Leung, Hei (Oxford University Press, 2014)
We consider genomic imputation for low-coverage genotyping-by-sequencing data with high levels of missing data. We compensate for this loss of information by utilizing family relationships in multiparental experimental crosses. This nearly quadruples the number of usable markers when applied to a large rice Multiparent Advanced Generation InterCross (MAGIC) study.